INTERFERENSI MORFOLOGI BAHASA JAWA KE DALAM BAHASA INDONESIA PADA TUTURAN DALAM SINETRON BANYAK JALAN MENUJU RHOMA TINGKAT 2 DI INDOSIAR - Asngadi Rofiq; Nita Nur Afida (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2020)
This study examines the morphological interference of Javanese into Indonesian which is found in the speech in the soap opera Many Paths to Rhoma Level 2 in Indosiar. This study aims to (1) determine the form of Javanese Morphological Interference into Indonesian. (2) to determine the factors that cause the Morphological Interference of Javanese into Indonesian which is carried out in the speech in the soap opera, There are Many Paths to Rhoma Level 2 in Indosiar. This research uses a qualitative descriptive research approach. The data were analyzed using the Matching method using the basic technique of Sorting the Determining Elements (PUP). The results of this study are in the form of Morphological Interference and the causes of Morphological Interference. The form of Morphological Interference contained in the speech on the soap opera Many Paths to Rhoma Level 2, namely in the form of Morphemic process interference and also Morphophonemic process interference. The factor that causes the Morphological Interference of Javanese into Indonesian in Speech in the soap opera Many Paths to Rhoma Level 2 is due to the habit of speakers using the first language.